2014
DOI: 10.1007/s00277-014-2023-2
|View full text |Cite
|
Sign up to set email alerts
|

The lymphoma-like polychemotherapy regimen “Dexa-BEAM” in advanced and extramedullary multiple myeloma

Abstract: Extramedullary disease (EMD) in multiple myeloma (MM) is characterised by an aggressive biology and an adverse prognosis especially when occurring at relapse. Due to the high proliferation found in EMD lesions, we analysed outcome data of patients treated with a lymphoma-type therapy not based on novel compounds, the Dexa-BEAM protocol. Retrospective analysis of MM patients having received Dexa-BEAM (including dexamethasone, carmustine, cytarabine, etoposide and melphalan) at our institution from January 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
2
17
0
2
Order By: Relevance
“…In these patients of highest risk, despite most intense treatments applied, response rates are being described as consistently poor (ranging from 24-54%) and overall survival times are disappointingly short (4-7 months) 3, 22, 23. Similarly in our cohort, time to disease relapse was relatively short in all studied patients with median progression-free and overall survival times of 54 and 223 days, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…In these patients of highest risk, despite most intense treatments applied, response rates are being described as consistently poor (ranging from 24-54%) and overall survival times are disappointingly short (4-7 months) 3, 22, 23. Similarly in our cohort, time to disease relapse was relatively short in all studied patients with median progression-free and overall survival times of 54 and 223 days, respectively.…”
Section: Discussionsupporting
confidence: 45%
“…In a previous study of our institution investigating patients with EMD prior to the carfilzomib era, patients were treated with intensive chemotherapy, such as VDT-PACE, VRD-ICE, RAD, VCDT, and autologous or allogeneic SCT, and we observed a median PFS and OS of two (95% CI, 0.08-3.92) and seven (95% CI, 3.56-10.43) months, respectively [11]. Additionally, Rasche et al reported a median PFS of four months in patients with extramedullary RRMM treated with DexaBEAM [17]. At our institution, the novel CXCR4-directed endoradiotherapy (ERT) has shown promising efficacy (ORR 75%) but no favorable survival outcome (median PFS 54 days, range 13-175 days and median OS 223 days, range 13-313 days) in extramedullary relapsed MM [42].…”
Section: Discussionsupporting
confidence: 51%
“…96 Evidence suggests that dexamethasone with carmustine, etoposide, cytarabine, and melphalan is an effective conditioning regimen, particularly in patients with extramedullary disease. 97 Bortezomib has been added to carmustine, etoposide, cytarabine, and melphalan in the setting of salvage transplantation and resulted in a 20% therapy-related mortality rate. 98 Melphalan remains the standard for transplantation, but the addition of novel agents to conditioning is being actively explored.…”
mentioning
confidence: 99%